On-line multi-residue analysis of fluoroquinolones and amantadine based on an integrated microfluidic chip coupled to triple quadrupole mass spectrometry. Issue 44 (2nd November 2020) - Tang, Minmin; Zhao, Yaju; Chen, Jing; Xu, Danke
Abstract : An on-line multi-residue qualitative and quantitative analysis method for fluoroquinolones and amantadine using an integrated microfluidic chip was developed prior to directly coupling to triple quadrupole mass spectrometry (QQQ-MS). Abstract : An on-line multi-residue qualitative and quantitative analysis method for fluoroquinolones and amantadine using an integrated microfluidic chip was developed prior to directly coupling to triple quadrupole mass spectrometry (QQQ-MS). Six parallel channels consisting of sample filtration units and micro solid phase extraction (micro-SPE) columns were present in the specifically designed microfluidic device. Firstly, the impurities in the sample solution were trapped by the micropillars in the filtration units. The solution passed through the micro-SPE units packed with hydrophilic–lipophilic balanced (HLB) particles, and then the two classes of drugs were enriched. After washing, the targets were eluted and immediately electrosprayed for MS analysis. This approach allowed effective filtration, enrichment, elution, and MS detection without the introduction of an additional separation step after SPE. Direct electrospray ionization (ESI)-MS in multiple reaction monitoring (MRM) mode could not only ensure the high sensitivity of quantitative analysis, but also achieved accurate qualitative analysis towards targets using the MRM ratios, reducing the possibility of false positives. Good linear relationships were obtained by the internal standard (IS) method with a linear range of 1–200 ng mL −1 ( R 2 > 0.992). The mean recoveries of the eight target analytes were from 85.2% to 122% with the relative standard deviation (RSD) ranging from 5.6% to 20.3%. All this demonstrated that the developed microfluidic device could be a useful tool for rapid detection in the field of food safety.